2019
DOI: 10.1080/09546634.2018.1473837
|View full text |Cite
|
Sign up to set email alerts
|

Patients preferences for different corticosteroid vehicles are highly variable

Abstract: There was wide variation in patient preference for topical medication vehicles used for treating psoriasis. Several vehicle characteristics were considered important to adherence. Given the marked variation in vehicle preference, topical treatment should be individualized according to patients' preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…In a clinical study aimed at establishing the patient’s preference among several topical corticosteroids, Felix et al, identifies an extensive variability, confirming the need to individualize the treatment. Subjects expressed the greatest concern for the absorption, messiness, feel on skin, and stains on fabrics; cost and side effects were the two most influential Determinants of Adherence and Quality of Life [ 57 ]. More recently, an indirect analysis comparing comments on the use of Cal/BD cream and foam showed that treatment with Cal/BD cream was associated with significantly greater satisfaction on the overall treatment vs. the foam since the cream resulted in ‘ease of application’, ‘not greasy’, and ‘felt moisturizing’ [ 58 ].…”
Section: Topical Vehicles and Patient’s Preferencesmentioning
confidence: 99%
“…In a clinical study aimed at establishing the patient’s preference among several topical corticosteroids, Felix et al, identifies an extensive variability, confirming the need to individualize the treatment. Subjects expressed the greatest concern for the absorption, messiness, feel on skin, and stains on fabrics; cost and side effects were the two most influential Determinants of Adherence and Quality of Life [ 57 ]. More recently, an indirect analysis comparing comments on the use of Cal/BD cream and foam showed that treatment with Cal/BD cream was associated with significantly greater satisfaction on the overall treatment vs. the foam since the cream resulted in ‘ease of application’, ‘not greasy’, and ‘felt moisturizing’ [ 58 ].…”
Section: Topical Vehicles and Patient’s Preferencesmentioning
confidence: 99%
“…Topikalna terapija kortikosteroidima je u drugoj polovini XX veka brzo i dobro prihvaćena od strane pacijenata jer je bila efikasna, jednostavnija za primenu i kozmetski prihvatljivija od prethodnih modaliteta (katrana, antralina), bez neprijatnog mirisa, oštećenja tkanina (odeće, posteljine), intenziviranja simptoma iritacije kože. Farmaceutska industrija razvila je brojne formulacije za primenu topikalne kortikosteroidne terapije, ali informacije o afinitetu pacijenata prema vrstama vehikuluma, kao i uticaju na adherenciju sa terapijom su oskudne 19,20 . Neoptimalna adherencija sa terapijom dovodi do neuspeha lečenja, nepovoljnih kliničkih ishoda, povećanja troškova.…”
Section: Afiniteti Pacijenata Prema Formulacijama Topikalnih Kortikos...unclassified
“…For example, one study found that preference for corticosteroid vehicles among psoriasis patients was highly variable and choice of vehicle was critical to adherence. 6 Another study highlighted differences in vehicle choice between younger and older age groups with psoriasis. 7 Given the limited data overall, it was our goal to determine if any patterns of preference existed by age, gender, or ethnicity, regardless of disease state or indication for topical product.…”
Section: Commentmentioning
confidence: 99%